AVAILABILITY AND UTILIZATION OF TEACHERS IN UNITY SCHOOLS IN NIGERIA - EGBORO, Paul Mukoro (Ilorin Journal of Education, 2023)
The study set out to examine the availability and utilization of teachers in Unity Schools in Nigeria. The population of the study was all the teachers in the 104 Unity Schools in the six geo[1]political zones of North East, North Central, North West, South South, South West, and South East of the country. Specifically, 3447 teachers in 36 (35%) out of the 104 Unity Schools in three geo[1]political zones of South South, South West, and South East were sampled. A Self -designed checklist was used to collect data for the study. The data collected were analyzed using simple percentages and bar-charts. Teachers’ availability and utilization was examined in terms of distribution by qualifications, teacher-student ratio using the Full Time Equivalent Teachers[1]Students ratio (FTETSR). The research findings revealed that teachers were over utilized in Unity Schools in Nigeria with teacher- student ratio of 1:70. Based on the findings, it was recommended that the Federal Ministry of Education should always make an equitable distribution of teachers to schools on the basis of school size/population and also recruit more teachers especially in the core subjects of Mathematics and English Language.